2021
DOI: 10.3389/fpsyg.2021.718700
|View full text |Cite
|
Sign up to set email alerts
|

Sound-Action Symbolism

Abstract: Recent evidence has shown linkages between actions and segmental elements of speech. For instance, close-front vowels are sound symbolically associated with the precision grip, and front vowels are associated with forward-directed limb movements. The current review article presents a variety of such sound-action effects and proposes that they compose a category of sound symbolism that is based on grounding a conceptual knowledge of a referent in articulatory and manual action representations. In addition, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 118 publications
2
17
0
Order By: Relevance
“…The results of this study mostly supported our views that the sound-magnitude effect and the grip-sound effect are based on overlapping mechanisms [ 39 ]. The same vowels and consonants that have been associated with large magnitudes in the sound symbolism literature ([ɑ], [o], [u], [æ], [k], [m] and [l]) also appear to be associated with the power grip responses.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The results of this study mostly supported our views that the sound-magnitude effect and the grip-sound effect are based on overlapping mechanisms [ 39 ]. The same vowels and consonants that have been associated with large magnitudes in the sound symbolism literature ([ɑ], [o], [u], [æ], [k], [m] and [l]) also appear to be associated with the power grip responses.…”
Section: Discussionsupporting
confidence: 87%
“…It has been proposed that many sound-symbolic phenomena can be based on the articulatory and/or acoustic properties of speech sounds [ 37 , 38 ]. We have previously proposed that the grip-sound effect and the sound-magnitude symbolism effect might be–to some degree–based on the same representational mechanisms [ 39 ]. The sound-magnitude symbolism refers to systematic mental associations between specific speech sounds and magnitude concepts [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, findings implicating a role of sound symbolism in language structure and function, including the ubiquity of sound-symbolic associations across multiple languages (Blasi et al, 2016), the higher frequency of rounded (pointed) phonemes in words signifying rounded (pointed) objects (Sidhu et al, 2021), the facilitation of word learning by sound symbolism (Nygaard et al, 2009), and the relative advantage for onomatopoeic words in aphasia (Meteyard et al, 2015), lead to the prediction that congruency effects would be found in classical language areas. Finally, brain regions mediating motor control and related somatosensory processing are also candidate loci for congruency effects, given findings suggesting close relationships between articulatory and manual movements (Vainio & Vainio, 2021, 2022, and acoustic similarities between speech and action sounds (Margiotoudi & Pulvermüller, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Embodied sounds in this study are understood as sounds associated with bodily sensations, bodily movements, and touch. Embodied nature of sound is related to the fact that sounds accompany actions and are processed together ( Vainio & Vainio, 2021 ). Sound characteristics (higher-lower pitch) affect hand movements (upper-lower hand locations; Salgado-Montejo et al., 2016 ).…”
mentioning
confidence: 99%